Antibacterial hydrogel dressings and their applications in wound treatment - Song, Xinyu (2023)
Antimicrobial hydrogels, both in semi-stiff sheets and amorphous form, have been extensively studied for wound management mainly owing to their high-water content, lower wound adherence, promoted autolysis debridement, epithelial migration, and granulation growth. Benefiting from the recent advances in materials science, biotechnology, and a growing understanding of wound microbiology, an extensive variety of antimicrobial hydrogels have been developed. These novel antimicrobial hydrogels can prevent and control microbial infection. In addition, they possess wound healing functions for improved wound management. This chapter will provide a comprehensive summary of the current studied antimicrobial hydrogels in literature and available hydrogel dressings in the market, including their design, fabrication method, and wound management efficacy in vitro or in vivo. The detailed and critical discussion of the advantages and disadvantages of each type of hydrogel dressing will provide insights into the future design of antimicrobial hydrogels for better management of wounds in clinical application.